A facile strategy to adjust SnO2/perovskite interfacial properties for high-efficiency perovskite solar cells. Issue 21 (18th May 2022) - Tao, Junlei; Yu, Zhaohui; Liu, Xiaoni; Xue, Jingwei; Shen, Jinliang; Guo, Hansong; Kong, Weiguang; Fu, Guangsheng; Yang, Shaopeng
Abstract : (1) The defects were passivated and the energy levels aligned at the SnO2 /perovskite interface by using EOAI. (2) A champion efficiency of 22.61% was realized for the 1.57 eV PSC and a PCE close to 20% was realized for the 1.68 eV PSC with higher stability. Abstract : The interface between the electron transport layer (ETL) and the perovskite film plays a vital role in the performance of perovskite solar cells (PSCs). Here, (2-hydroxyethyl)amine hydroiodide (EOAI) is employed to regulate the interface properties at the SnO2 /perovskite. The –NH3 + positive and I − negative ion groups in EOAI, which are anchored on the surface of SnO2 through –OH groups, can passivate the interface defects of perovskite films. Besides, the modified ETL has a smaller work function (WF) and E VB than pristine ones, which contributes to efficient charge transport and collection. Furthermore, the introduction of EOAI can also improve the crystallinity of the perovskite layer. As a result, PSCs with EOAI-modified SnO2 produce a champion power conversion efficiency (PCE) of 22.61%, and an improved environmental stability. At the same time, the 1.68 eV wide-band gap perovskite solar cell achieved a PCE close to 20% and the semitransparent device also achieved an efficiency of over 17%.